2021
DOI: 10.1017/s0144686x21001070
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of successful ageing among older adults aged 75+: a systematic review with a narrative synthesis of mixed studies

Abstract: Older adults 75 and above are a fast-growing segment of the population. However, few studies have investigated what it means to age successfully from their perspective. This group of older adults face challenges that might characteristically differ from younger older adults. Therefore, the aim of this study was to conduct a systematic review of the perspectives of older adults aged 75 and above regarding what it means to age successfully and to summarise the findings through a narrative synthesis. We also aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Autonomy, one of the most important human needs, de ned by Ryan and Deci as the experience of choice 30 , is associated with many positive outcomes, such as satisfaction with life and well-being 31 . Research has shown that older people consider autonomy to be an essential criterion of SA 22 . In our study, autonomy is de ned as subjective evaluation of independence and freedom of choice 32 .…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomy, one of the most important human needs, de ned by Ryan and Deci as the experience of choice 30 , is associated with many positive outcomes, such as satisfaction with life and well-being 31 . Research has shown that older people consider autonomy to be an essential criterion of SA 22 . In our study, autonomy is de ned as subjective evaluation of independence and freedom of choice 32 .…”
Section: Current Studymentioning
confidence: 99%
“…These groups of elderly adults, referred to as Young-Old (Y-O) and Old-Old (O-O), are also distinguished in research on good aging 21 . Recently, researchers have been paying more attention than before to the 75 + age group, noticing its speci city in the context of self-rated SA 12,22 . Still, the number of empirical studies on these issues is very limited, especially those that aim at comparing Y-O and O-O groups.…”
Section: Introductionmentioning
confidence: 99%
“…With life expectancy continuing to rise, the impact of these conditions will only become more burdensome. Therefore, to identify more effective healthy brain ageing strategies and interventions [ 2 , 3 ], we need to deepen our understanding of the factors that promote or hinder these ageing-related brain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To answer this question, lifespan psychologists, neuroscientists, and epidemiologists have identified resilience factors that may promote successful aging ( Carstensen, 2006 ; Park and Reuter-Lorenz, 2009 ; Brassen et al, 2012 ; Mather, 2016 ; Heckhausen et al, 2019 ). The concept of successful aging is hereby often equated with emotional health ( Badache et al, 2023 ), although it has undergone different interpretations since its introduction in the early 1960s ( Havighurst, 1961 ). There are three well-known psychobiological models of successful aging.…”
Section: Introductionmentioning
confidence: 99%